A small state's guide to influence in world politics - Long, Tom. (Oxford Oxford University Press, 2022)
Small states are crucial actors in world politics. They attract outsized attention from great powers, populate international organizations, and shape international norms. Despite that, they have been relegated to a second tier of International Relations scholarship. Many explanations of international politics are largely silent on small states. When mentioned, small states often are treated as victims of great power aggression or free riders on great powers' good will. Some small states fit that picture of impotence. But many others are strikingly successful-wealthy, cosmopolitan, and even influential. This book asks, when and how can small states achieve their goals in international relations? It puts small states' relationships at the center of the answer. Small states are defined by their position as the weaker actor vis-a-vis large states. Small states themselves, as well as their opportunities and constraints, are shaped by these power asymmetries. How might they "overcome" that asymmetry in pursuit of their goals? This book offers a contextualized explanation of how small states can assess the conditions of their asymmetrical relationships, identify opportunities, and shape effective strategies. The book offers tools for scholars and policymakers. It proposes an analytical approach and develops a typological theory of when and how small states might achieve greater influence. The book then deploys that theory in some twenty cases studies drawn from Africa, Asia, Europe, and Latin America, covering issues of security, international political economy, and international institutions, norms, and laws
Keywords: Small states are crucial actors in world politics. Yet, they have been relegated to a second tier of International Relations scholarship. In A Small State's Guide to Influence in World Politics, Tom Long shows how small states can identify opportunities and shape effective strategies to achieve their foreign policy goals. To do so, Long puts small states' relationships at the center of his approach. Although small states are defined by their position as materially weaker actors vis-a-vis large states, Long argues that this condition does not condemn them to impotence or irrelevance. Drawing on typological theory, Long builds an explanation of when and how small states might achieve their goals. The book assesses a global range of cases-both successes and failures-and offers a set of tools for scholars and policymakers to understand how varying international conditions shape small states' opportunities for influence